A new species of Stenampyx Karsch, 1890 from East Africa (Orthoptera: Tettigoniidae, Pseudophyllinae, Phyllomimini)—evidence of a former connection of West-Central and East African forests - Hemp, Claudia (Zootaxa, 2020)
A new Stenampyx, S. viridiflavum n. sp., is described from Tanzania. Stenampyx was monotypic and known from Central to West African forests. As with the genus Pseudotomias Hemp, the newly described species in Stenampyx shows a close relationship to the Central and East African forest fauna.